The dynamic price function discovery between FBM KLCI Index (KLCI) and FBM KLCI Futures (FKLI): evidence pre and during COVID-19 pandemic in Malaysia - Azmin, Muhammad Auquasyah (2023)
The dynamic price function discovery within the lead-lag relationship in Malaysia between FTSE Bursa Malaysia Kuala Lumpur Composite Index (KLCI) and FTSE Bursa Malaysia Kuala Lumpur Composite Index futures (FKLI) before and during the COVID-19 pandemic has been empirically studied in this thesis. The daily closing price of the spot and futures market with maturities of spot-month, next-month, next quarter, and following two quarterly prices and the price discovery role of both markets has been examined. According to the empirical findings, KLCI and FKLI had a long-run cointegration and equilibrium relationship both before and during the COVID-19 pandemic period. Furthermore, the long-run association has been confirmed to exist between spot and futures market before and during the COVID-19 pandemic. Overall, the empirical results confirmed the role of spot market as price function discovery for both observation periods. This implies that investors and potential investors in Malaysia stock market will rely on information embedded in spot market to trade in futures market. Overall, the research has shown that the lead-lag relationship between the spot and futures markets invalidates the Efficient Market Hypothesis idea. Thus, the investors are now assured to use futures as the market predictors for the future underlying price, although there might safeguard their position, and the latest price discovery function has been documented.